Experimental verification of a floating ocean-current turbine with a single rotor for use in Kuroshio currents. (June 2016) - Shirasawa, Katsutoshi; Tokunaga, Kohei; Iwashita, Hidetsugu; Shintake, Tsumoru
Abstract: Ocean currents have excellent potential as future renewable energy resources. In order to harness the kinetic energy of marine currents, we propose a new ocean-current turbine. In general, ocean currents have sufficiently large cross sections. Thus, the turbines are moored to the seabed and function like kites in the water flow. In the future, turbines will be installed approximately 100 m deep to avoid the influence of surface waves; this is especially important during typhoons. To operate such turbines in the middle layer of a marine current, it is necessary to cancel the resulting rotor torque. Therefore, our turbine is designed with a float at its top and a counterweight at its bottom. Owing to buoyancy and gravity, the turbine maintains a stable position. We describe towing experiments carried out to confirm the float and counterweight configuration and show that the results verify hydrostatic stability and electric power generation for the proposed turbine. Highlights: We propose a new ocean-current turbine for harnessing the energy of marine currents. Our turbine is moored to the seabed and captures water flow at a current's middle layer. Our turbine is designed with a float and counterweight to cancel the developed rotor torque. Towing experiments were conducted to verify the float and counterweight configuration. High hydrostatic stability and reliable electric power generation were confirmed.